Na2CoPO4F as a pseudocapacitive anode for high-performance and ultrastable hybrid sodium-ion capacitors. (10th May 2020) - Or, Tyler; Kaliyappan, Karthikeyan; Li, Gaoran; Abureden, Salah; Bai, Zhengyu; Chen, Zhongwei
Abstract: Sodium-ion capacitors (NICs) reported in the literature demonstrate relatively poor cycle retention (<90% after 10, 000 cycles) and rate performance, which is not ideal for proposed applications such as regenerative brake charging. In this work, a 3 V NIC was fabricated using Na2 CoPO4 F (NCPF) as a next-generation anode and commercial activated carbon (AC) as the cathode in an organic electrolyte. The constructed NCPF//AC NIC exhibited exceptional rate performance, retaining 78% of its energy density (corresponding to 24 Wh kg −1 ) when the power density was ramped from 125 to 5000 W kg −1 . In addition, its long-term stability when cycled from 0 to 3 V is among the highest reported in the literature, retaining 93% of its energy density (24 Wh kg −1 ) after 100, 000 cycles at 1 kW kg −1 . Furthermore, at an elevated voltage range of 0–3.25 V, the NIC retained 80% of its energy density (26 Wh kg −1 ) after 30, 000 cycles at 375 W kg −1 . The performance is ascribed to the kinetic compatibility between the adsorptive cathode and pseudocapacitive anode, where pseudocapacitance is enhanced by the nanosized morphology on the surface of NCPF. The NIC system reported herein demonstrates supercapacitor-type benchmarks while also possessing a higher energy density. Graphical abstract: Image 1 Highlights: Na2 CoPO4 F synthesized displayed an improved half-cell cycle stability in the cathodic (2–5 V vs Na/Na + ) and anodic (0–3 V vs Na/Na + ) region. The Na2 CoPO4 F//AC sodium-ion capacitor (NIC) cell displayed exceptional cycle stability and rate performance at a high voltage range. The charge-storage mechanisms were examined through XRD, XPS, and EDX characterization pre- and post-cycling. The Nyquist spectra throughout long-term cycling (100, 000 cycles) reveal that the bulk and charge-transfer impedance is stable.